Hydrologically Informed Machine Learning for Rainfall‐Runoff Modeling: A Genetic Programming‐Based Toolkit for Automatic Model Induction - Chadalawada, Jayashree (American Geophysical Union (AGU), 2020)
10.1029/2019wr026933